The impact of macroprudential policies on capital flows in CESEE. (December 2021) - Eller, Markus; Hauzenberger, Niko; Huber, Florian; Schuberth, Helene; Vashold, Lukas
Highlights: Studies dynamic effects of macroprudential policy (MPP) on macrofinancial variables. Uses novel regime-switching factor-augmented VAR model to identify policy shifts. Includes intensity-adjusted index for MPPs tracking strength of adjustments. Credit growth and capital inflows decrease following a tightening MPP shock. Reactions to MPP tightening are stronger in a low-interest rate environment. Abstract: In line with recent policy discussions on the use of macroprudential policies (MPPs) to respond to cross-border risks arising from capital flows, this paper tries to quantify which impact MPPs had on capital flows in Central, Eastern and Southeastern Europe (CESEE). This region experienced a substantial boom-bust cycle in capital flows amid the global financial crisis and policymakers had been quite active in adopting MPPs already before that crisis. To study the dynamic responses of capital flows to a tightening in the macroprudential environment, we propose a novel regime-switching factor-augmented vector autoregressive (FAVAR) model and include an intensity-adjusted macroprudential policy index to identify MPP shocks. Our results suggest that tighter MPPs translate into negative dynamic reactions of domestic private sector credit growth and gross capital inflow volumes in a majority of the countries analyzed. Level and volatility responses of capital inflows are often correlated positively, suggesting that if MPPs were successful in reducing capital inflows, they would also contribute to lower capital flow volatility. We also provide evidence that the effects of MPP tightening are in most cases stronger in an environment characterized by low interest rates, suggesting that MPPs would be more effective if conventional monetary policy were facing constraints.